Strengthening digital marketing in empowering typical culinary business actors as tourism potential in Meranjat Village, Ogan Ilir - Ermanovida Ermanovida; Katriza Imania; Tuty Khairunnisyah; Aulia Utami Putri (Community Empowerment, 2023)
The purpose of this community service activity is to increase understanding of digital marketing in empowering typical culinary business actors as tourism potential in Meranjat Village, Ogan Ilir Regency. The method used is counseling and training on business development and digital marketing as well as question and answer activities. The results obtained in this activity are that there are several culinary business potentials in Ogan Ilir Regency which can be a source for developing tourism and the number of existing culinary business actors is also quite a lot. In addition, there was an increase in participants' knowledge regarding the importance of promotion and innovation of culinary products.